(untitled) (Journal of Contemporary Philology, 2020)
This paper aims to describe the differences in the use of the definite article in titles and subtitles. The research was conducted on a corpus of titles and subtitles excerpted from different types of discourse: written works of art and catalogues of theatre and film art. Titles and subtitles being specific language phrases are condensations of a longer text which follows below the title, and they are expected to report the key words of the text. Therefore, the use of the definite article in titles and subtitles besides having grammatical function, also it has a stylistic function. The analysis was done by examining instances of titles and subtitles from Macedonian written works translated into English and vice versa. The titles and subtitles often deviate from the standard language norm by the omission of the definite article. The results show that there are Macedonian titles with NPs marked with the definite article, which can be translated into English with NPs without the definite article, and Macedonian titles with NPs not marked with the definite article, which can translated into English with NPs with the definite article. We have concluded that English titles containing NPs with the definite article can be translated into Macedonian with NPs without an article and English titles containing NPs without the definite article can be translated into Macedonian with NPs with articles.